2014
DOI: 10.1042/bst20140180
|View full text |Cite
|
Sign up to set email alerts
|

PKCθ-regulated signalling in health and disease

Abstract: Protein kinase Cθ (PKCθ) is a key enzyme in T-lymphocytes where it plays an important role in signal transduction downstream of the activated T-cell receptor (TCR) and the CD28 co-stimulatory receptor. Antigenic stimulation of T-cells triggers PKCθ translocation to the centre of the immunological synapse (IS) at the contact site between antigen-specific T-cells and antigen-presenting cells (APCs). The IS-residing PKCθ phosphorylates and activates effector molecules that transduce signals into distinct subcellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…The stable activation and membrane translocation of PKCθ requires Vav and phosphatidylinositol 3-kinase (PI3K) activation, triggered by the CD28 costimulatory signal, in addition to TCR/CD3 signal (47). PKCθ, a Ca ++ -independent, phospholipid-dependent PKC isoform, is a central player in the immunological synapse, responsible for the activation of AP-1 and NF–κB downstream of the TCR (48). In this study, we observed that activation of CD8+T-cells with PMA and ionomycin, which directly and potently stimulate the activity of PKCs (47), increases the levels of Notch1 and consequently its activity.…”
Section: Discussionmentioning
confidence: 99%
“…The stable activation and membrane translocation of PKCθ requires Vav and phosphatidylinositol 3-kinase (PI3K) activation, triggered by the CD28 costimulatory signal, in addition to TCR/CD3 signal (47). PKCθ, a Ca ++ -independent, phospholipid-dependent PKC isoform, is a central player in the immunological synapse, responsible for the activation of AP-1 and NF–κB downstream of the TCR (48). In this study, we observed that activation of CD8+T-cells with PMA and ionomycin, which directly and potently stimulate the activity of PKCs (47), increases the levels of Notch1 and consequently its activity.…”
Section: Discussionmentioning
confidence: 99%
“…By regulating targeted signaling pathways, PKCs are critical for maintaining the cellular biological processes such as cell proliferation, migration, differentiation, apoptosis and autophagy [ 4 , 16 , 17 ]. Expression alteration and dysregulation of PKCs are often associated with many human diseases including diabetes, autoimmune diseases, neurodegenerative diseases, and cardiovascular diseases [ 18 ]. Altered PCK expression levels have also been indicated to be associated with a range of human malignant cancers [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in addition to TLR-dependent mechanisms, the presence of high plasma NEFAs increases FA flux in skeletal muscle cells, exceeding their oxidation capacity, which then leads to the accumulation of FA derivatives such as diacylglycerol (DAG) and ceramide [35] that ultimately attenuate insulin signaling. DAG activates protein kinase Cθ (PKCθ) in skeletal muscle [36], which in turn activates IKK-NF-B. Both kinases phosphorylate IRS-1 on serine residues, attenuating the insulin signaling pathway.…”
Section: Ppareffects In Skeletal Muscle Cellsmentioning
confidence: 99%